Tribal Higher Education and Social Inclusion: A Critical Review of Access, Diversity, and Equity Frameworks for Inclusive Growth in the Digital Era (International Journal of Scientific Research in Science and Technology, 2025)
Tribal communities in India remain significantly underrepresented in higher education despite decades of affirmative measures. While constitutional provisions and policy reforms have expanded formal access, challenges of remoteness, financial constraints, linguistic exclusion, and cultural alienation continue to limit participation. Recent initiatives such as Digital India and the National Education Policy 2020 promote technology-enabled learning as a pathway to overcome these barriers. This study synthesizes 80 peer-reviewed works and 12 policy reports (2000–2025) using a PRISMA-guided scoping method to critically examine four dimensions: access and participation, curricular and pedagogical inclusiveness, diversity and representation, and equity in outcomes. Findings reveal a “digital double bind,” where ICT platforms simultaneously expand reach and risk deepening inequalities if cultural, linguistic, and infrastructural barriers persist. The review develops an integrated framework Digital Pathways that positions technology as both an enabler and potential reproducer of exclusion. The paper contributes a set of operational indicators for policy evaluation, recommendations for inclusive digital reform, and a future research agenda that emphasizes intersectional analysis and longitudinal impact studies.